What is the relevance of Ikaros gene deletions as a prognostic marker in pediatric Philadelphia-negative B-cell precursor acute lymphoblastic leukemia? - Palmi, Chiara (Ferrata Storti Foundation, 2013)
New prognostic markers are needed for upfront identification of patients with acute lymphocytic leukemia with a high risk of relapse or who are not likely to respond to the most aggressive chemotherapy. We focused our analysis on Ikaros (IKZF1) gene deletions in a homogeneous cohort of 410 pediatric patients with Philadelphia chromosome-negative, B-cell precursor acute lymphoblastic leukemia enrolled in Italy into the AIEOP-BFM ALL2000 study. We confirm their reported poor prognostic value, although the associated event-free survival was relatively high (approximately 70%). The difference in the cumulative incidence of relapse between patients positive or not for IKZF1 deletions was not marked: 24.2% (5.9) versus 13.1% (1.8) overall and 23.9% (6.6) versus 16.5% (2.5) in the intermediate-risk subgroup. In line with this, IKZF1 deletions were not an independent prognostic factor for the hazard of relapse. Most IKZF1-deleted cases stratified in the high-risk group relapsed, suggesting that once identified, patients with these deletions require an alternative treatment. In conclusion, the need of and benefit from introducing IKZF1 deletions as an additional stratification marker for patients with Philadelphia-negative B-cell precursor acute lymphoblastic leukemia remain questionable.